The Shadow Of The Future: Effects Of Anticipated Interaction And Frequency Of Contact On Buyer-Seller Cooperation - Heide, Jan B.; Miner, Anne S. (Academy of Management Journal, 1992)
This research examined cooperation between 136 industrial buyers and suppliers. We identified four domains of potential cooperation: flexibility, information exchange, shared problem solving, and restraint in the use of power. Using an iterated games framework, we predicted that (1) anticipated open-ended future interaction, or extendedness, and (2) frequency of contact will increase the chances that a pattern of cooperative behavior will occur, but (3) performance ambiguity will decrease such chances. Regression analysis results indicated that extendedness and frequency are associated with joint cooperation. Neither simple structural theories of cooperation nor interactive models stressing commitment would fully predict these results, which support the potential value of interactive perspectives on interorganizational cooperation in particular and on interorganizational relationships in general.